American paradise : hidden ironies, contradictions, illusions, and delusions, paradoxes, dilemmas, and absurdities in American life - Huer, Jon (University Press of America, 2010)
"The way we live, work, and die--alone and with other Americans--have so many hidden layers that we might as well say that there are two Americas: one we think we know and the other virtually unknown to us."--Page 4 of cover